Mapeamento da diversidade de Drosofilídeos no mosaico de paisagem em Igarapé-Açu, região bragantina - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2001)
This project aims to map the diversity of drosolillids in different habitat units within a landscape mosaic with varying degrees of anthropogenic disturbance related to family farming activities in the municipality of Igarapé-Açu. The habitats analyzed were old capoeira (secondary vegetation over 30 years old - 2 sites), rich capoeira (enriched with legumes - 2 sites), poor capoeira (less than 20 years old - 2 sites), passion-fruit plantation (2 sites), gallery forest (remnant of primary forest adjacent to water courses - 1 site) and backyard (area surrounding the settler's house - 1 site). To collect insects, traps containing banana bait were used, suspended 50 cm from the ground. At the end of the collections 3058 individuals belonging to 28 species of Drosophilidae were obtained in the six habitats analyzed. The proportion of abundance of the drosolillids, measured by the number of individuals sampled per trap, was 25.3% in poor shrublands, 20.0% in old shrublands, 17.2% in backyards, 16.0% in rich shrublands, 15.5% in the forest, and 6.0% in plantations. Almost half of the individuals, 46.8% were Drosopbila malerkotliana. This species was mainly concentrated in disturbed forest habitats. The diversity expressed by the Shannon index for the agricultural landscape analyzed (H'= 1.5) was low and the total number of species estimated for the region, based on accumulation curves ranged between 32 and 37. The similarity of fauna composition was higher among the more disturbed forest habitats and lower between primary forest and backyards, suggesting that the patterns of abundance and diversity of drosophilids clearly reflect the degree of environmental integrity.
Mapping the diversity of Drosophilids in the landscape mosaic in Igarapé-Açu, Bragantine region
Keywords: Drosofilídeos; Drosopbila malerkotliana; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA